Atg1-mediated autophagy suppresses tissue degeneration in pink1/parkin mutants by promoting mitochondrial fission in Drosophila - Ma, Peng (Mol Biol Cell, 2018)
Mitochondrial dysfunction is considered a hallmark of multiple neurodegenerative diseases, including Parkinson’s disease (PD). The PD familial genes pink1 and parkin function in a conserved pathway that regulates mitochondrial function, including dynamics (fusion and fission). Mammalian cell culture studies suggested that the pink1/parkin pathway promotes mitophagy (mitochondrial autophagy). Mitophagy through mitochondrial fission and autolysosomal recycling was considered a quality control system at the organelle level. Whether defects in this quality control machinery lead to pathogenesis in vivo in PD remains elusive. Here, we found that elevating autophagy by atg1 overexpression can significantly rescue mitochondrial defects and apoptotic cell death in pink1 and parkin mutants in Drosophila. Surprisingly, the rescue effect relied both on the autophagy–lysosome machinery and on drp1, a mitochondrial fission molecule. We further showed that Atg1 promotes mitochondrial fission by posttranscriptional increase in the Drp1 protein level. In contrast, increasing fission (by drp1 overexpression) or inhibiting fusion (by knocking down mitofusin [mfn]) rescues pink1 mutants when lysosomal or proteasomal machinery is impaired. Taken together, our results identified Atg1 as a dual-function node that controls mitochondrial quality by promoting mitochondria fission and autophagy, which makes it a potential therapeutic target for treatment of mitochondrial dysfunction–related diseases, including PD.